PENGARUH KUALITAS PRODUK, DESAIN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIANKOPIAH MEREK GADING GAJAH GRESIK - MUSTIKASARI, WENING (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Todays business is growing rapidly, more and more companies established and produce the same product as others. The occured phenomenon is that kopiah (kind of a cap worn by moslem men especially, and by Indonesian men generally) is not only worn by Muslim to worship. But it is also used as official headdress when men attending formal events. From various kinds of kopiahbrands, Gading Gajah brand are becoming one of the public choices among other kopiah brands. The aim of this study is to determine the effect of product quality, product design and price simultaneously and partially on product purchase decisions of kopiahwith Gading Gajah brand. Results of studies gained by using the F test showed that simultaneously product quality, product design and price affect the purchase decisions of consumers. It can be seen from the Adjusted R Square of 0.681. Then through the t-test, it is known that the quality of products significantly influence purchase decisions at 2,332 with a significance value of 0.021 <0.05 or 5%. Product design also significantly affect the purchase decisions of 11.411 with a significance value of 0.000 <0.05 or 5%, while the price has a t value of 2.205 was also significantly affect purchase decisions with significance value of 0.029 <0.05 or 5 %. Partially, product design variable has a greater effect on purchase decisions of consumers. Keywords: Quality Product,Design Product, Price, Purchase Decision